"If Old Heads Could Talk": Sango Healers in the Caribbean - Glazier, Stephen D. (Anthropologica, 2012)
This paper examines Sango beliefs and representa tions of illness with a primary focus on Sango hëaling practices. In addition, it explores ritual borrowing, divination and spirit possession within the Sango tradition and examines relation ships between Sango healers and Western biomedical practitio ners. Lastly, I will address the resurgence of Sango in contem porary Caribbean societies and implications of this resurgence for biomedicine and health care in the region.